Molecular profiling of the lateral habenula in a rat model of depression. - Trine Christensen; Line Jensen; Elena V Bouzinova; Ove Wiborg (PLoS ONE, 2013)
OBJECTIVE: This study systematically investigated the effect of chronic mild stress and response to antidepressant treatment in the lateral habenula at the whole genome level. METHODS: Rat whole genome expression chips (Affymetrix) were used to detect gene expression regulations in the lateral habenula of rats subjected to chronic mild stress (mild stressors exchanged twice a day for 8 weeks). Some rats received antidepressant treatment during fifth to eights week of CMS. The lateral habenula gene expression profile was studied through the gene ontology and signal pathway analyses using bioinformatics. Real-time quantitative polymerase chain reaction (RT-PCR) was used to verify the microarray results and determine the expression of the Fcrla, Eif3k, Sec3l1, Ubr5, Abca8a, Ankrd49, Cyp2j10, Frs3, Syn2, and Znf503 genes in the lateral habenula tissue. RESULTS: In particular we found that stress and antidepressant treatment affected intracellular cascades like growth factor receptor signaling, G-protein-coupled receptor signaling, and Wnt signaling - processes involved in the neuroplastic changes observed during the progression of depression and antidepressant treatment. CONCLUSION: The present study suggests an important role of the lateral habenula in the development of depression-like conditions and correlates to previous studies demonstrating a significant role of the lateral habenula in depressive-like conditions and antidepressant treatment.